2004
DOI: 10.1038/sj.onc.1207457
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic switch in Rb+/− mediated neuroendocrine tumorigenesis

Abstract: Rb þ /À mice develop a complex spectrum of neuroendocrine tumors on a mixed genetic (129Sv  C57BL/6) background. To understand how the 129Sv and C57BL/6 contributions affect Rb þ /À tumorigenesis, we serially backcrossed Rb þ /À animals to the 129Sv or C57BL/6 strain, and analysed their pathological profiles. Strikingly, the length of survival and the penetrance, severity and multiplicity of neuroendocrine tumors switch dramatically between Rb þ /À animals from the two genetic backgrounds. In fact, the 129Sv … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…These include Rb, Ccdn1/cyclinD1 , a cyclin-dependent kinase ( Cdk4 ) and a few CDKIs, p18 , p21 and p27 . Although mouse models with germline Rb loss ( Rb +/− ) mainly show intermediate lobe pituitary tumors, Rb +/− mice in the C57 background show high penetrance for anterior pituitary tumors [38]. Mouse strain backgrounds did not have any effect on the development of prolactinomas in the MEN1 mouse models: mouse background C57/129 [21,22], C57/129SvTacFBR (TSM) or C57BL/6 (dN3–8) [19,26] or 129/Ola,129/Sv (Table 1) [20].…”
Section: Tumors Of Men1 In Mouse Models Of Cell Cycle Control Genes Wmentioning
confidence: 99%
“…These include Rb, Ccdn1/cyclinD1 , a cyclin-dependent kinase ( Cdk4 ) and a few CDKIs, p18 , p21 and p27 . Although mouse models with germline Rb loss ( Rb +/− ) mainly show intermediate lobe pituitary tumors, Rb +/− mice in the C57 background show high penetrance for anterior pituitary tumors [38]. Mouse strain backgrounds did not have any effect on the development of prolactinomas in the MEN1 mouse models: mouse background C57/129 [21,22], C57/129SvTacFBR (TSM) or C57BL/6 (dN3–8) [19,26] or 129/Ola,129/Sv (Table 1) [20].…”
Section: Tumors Of Men1 In Mouse Models Of Cell Cycle Control Genes Wmentioning
confidence: 99%
“…Intriguingly, a recent new mouse model of pituitary tumorigenesis, the knock-in mice depleted of the Cdk inhibitory function of p27, develops pituitary adenomas larger and more vascular, causing more damage to surrounding tissue than those developing in p27-null mice (Besson et al 2007). Interestingly, a recent study highlighted the importance of the mouse strain on pituitary tumor evolution, since it showed that 129Sv animals are inherently predisposed to IL pituitary tumors and that Rb C/K mice in a C57BL/6 background develop high-penetrance anterior pituitary (AP) tumors (Leung et al 2004).…”
Section: The Cell Cyclementioning
confidence: 99%
“…In contrast to humans, in whom individuals who inherit one defective copy of pRB gene have a roughly 90% likelihood of developing retinoblastoma at an early age (Matsunaga 1980), mice heterozygous for pRB did not develop retinoblastoma but instead developed pituitary tumors by the age of 12 months (Jacks et al 1992; Table 1). Tumor incidence and histological phenotype of the tumors was highly dependent on the mouse strain suggesting additional modifier genes in pituitary tumor development (Leung et al 2004). Tumor incidence provoked by the partial deletion of pRB is partially reverted by a mutation in pRB effectors such as E2f1 (Yamasaki et al 1998) or E2f4 (Lee et al The genetic analysis of pRB in the mouse clearly demonstrated a tumor suppressor function for this protein, and specifically in endocrine organs such as the pituitary.…”
Section: Pituitary Function and Mouse Models Of Cell Cycle Deregulationmentioning
confidence: 99%